Increasing Difference in Interannual Summertime Surface Air Temperature Between Interior East Antarctica and the Antarctic Peninsula Under Future Climate Scenarios - Rui Mao; Seong‐Joong Kim; Dao‐Yi Gong; Xiaohong Liu; Xinyu Wen; Liping Zhang; Feng Tang; Qi Zong; Cunde Xiao; Minghu Ding; Sang‐Jong Park (Geophysical Research Letters)
Abstract In this study, using the Climate Model Intercomparison Project 5 (CMIP5) simulations and by empirical orthogonal function (EOF) analysis, the first mode of variability in interannual surface air temperature (SAT) in Antarctica (EOF1) was examined for the period between 1979–2004 and 2051–2099 during the austral summer. The ensemble mean of EOF1 of the CMIP5 models shows a positive SAT anomaly over the northern Antarctic Peninsula (AP) and a negative SAT anomaly over Eastern Antarctica (EA) in both periods. A poleward expansion of the AP positive anomaly and an increase in the negative anomaly over interior EA are expected in 2051–2099, resulting in a larger difference of interannual SAT between interior EA and the AP in 2051–2099 than in 1979–2004. The increasing difference in the interannual SAT is consistent with a larger magnitude of the SAM‐related circulation anomalies in the future.